Characterization of Escherichia coli from Captive Wild Animals for ESBL Production, Phylo-grouping and Virulence - Kolhe, Rahul; Gondake, Rahul; Waskar, Vikas; Mote, Chandrashekhar; Budhe, Mrunalini; Jaiswal, Shreyash (International Journal of Livestock Research, 2023)
In this study, 59 fecal samples were collected from wild animals in captivity and 34 E. coli were isolated (57.62%). Out of 34 isolates, 12 (35.29%) were DEC strains belonging to ETEC and EPEC pathotypes. ETEC strains were detected in spotted deer, grey cockatiel, and an Indian gaur. While EPEC strains were detected in hippopotamus, jackals, barking deer, and nilgai. E. coli mainly belongs to B2 phylogroups. The study revealed the detection of multi-drug resistant as well as ESBL type of E. coli in zoo animals. E. coli were resistant to tetracycline (97.05%), ceftriaxone (94.11%), ceftazidime (88.23%), cefoxitin, and ceftazidime plus clavulanic acid (79.41%). However, sensitivity to ertapenem, imipenem, and colistin was recorded. E. coli isolated from jackal, nilgai and elephant were highly sensitive to almost all the used antimicrobials. About 38.23% of strains were ESBL-producing and detected from barking deer, spotted deer, penguins, tiger, jackal, blackbuck, chinkara, India gaur, hanuman langur, and elongated tortoise. Some strains also showed colistin and MBL + AmpC type of resistance as estimated by the Ezy MIC kit. ESBL-positive strains were also studied for the presence of beta-lactam genes, and only blaTEM was detected.